Labour Resources in Kazakhstan and Uzbekistan: A Comparative Study - Krystyna GOMÓLKA (Communications of International Proceedings, 2022)
The aim of the paper is to show the transformation and comparison of labour resources in Kazakhstan and Uzbekistan using the following methods: deductive data analysis, observation of changes in the structure of resources based on publicly available macroeconomic data. During the two decades of the 21st century, both countries experienced population growth which translated into an increased number of persons of working age. In both countries, men were more active in the labour market and more than half of women were inactive. Both countries have seen an increase in the gross enrolment ratio at primary and secondary levels. In Kazakhstan the number of people with higher education fluctuated and in Uzbekistan it slowly increased. Unemployment decreased in both countries as a result of growing economy and economic migration. The net migration rate in both countries was negative, which affected the countries' labour resources, which reduced the workforce in Kazakhstan and Uzbekistan.
Keywords: labour resources; Kazakhstan; Uzbekistan; labour market; unemployment